1996
DOI: 10.1161/01.cir.93.10.1784
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Adhesion to the Coronary Microvasculature During Ischemia and Reperfusion in an In Vivo Canine Model

Abstract: Reperfusion, compared with ischemia alone, promotes the rapid accumulation of leukocytes in the coronary microvasculature of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 25 publications
0
39
0
3
Order By: Relevance
“…Exuberant neutrophil adhesion in the microvasculature is implicated in a variety of inflammatory diseases ranging from arthritis to ischemia-reperfusion injury [27,28]. In SCD, elevated leukocyte counts correlate with greater risk of complications and mortality [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Exuberant neutrophil adhesion in the microvasculature is implicated in a variety of inflammatory diseases ranging from arthritis to ischemia-reperfusion injury [27,28]. In SCD, elevated leukocyte counts correlate with greater risk of complications and mortality [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion of platelets to circulating myeloid leukocytes in vitro and in vivo is related to platelet activation (26). It is known that reperfusion of the ischemic myocardium often leads to rapid accumulation and adhesion of leukocytes to the endothelium, which are supposed to be the initial steps of leukocyte-mediated reperfusion injury (27,28). We might speculate that patients with a higher MPV have a higher potential for platelet-leukocyte interaction and thus, are more prone to platelet-activated, leukocyte-mediated reperfusion injury.…”
Section: Myocardial Infarction; Mpv Mean Platelet Volume; Wbc Whitmentioning
confidence: 99%
“…Although there was no difference in no-reflow zones between the neutropenic animals and the control group in a gerbil cerebral ischemia model, 36,37 other studies showed that reperfusion leads to rapid accumulation of leukocytes in the microvasculature of the dog heart. 38 This may be mediated by CD18-dependent leukocyte adhesion 39 and may play some role in the genesis of the no-reflow phenomenon. Byrne et al 40 found that reperfusion with leukocyte-depleted blood may reduce cardiac no reflow.…”
Section: Pathophysiologymentioning
confidence: 99%